(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The prevalence of head lice (Pediculus humanus capitis) infestation and malnutrition affect among the children (1 to 7 years) in the area of Mirpur Bihari Camp, Dhaka was observed. A total of 300 children were examined during February 2011 to January 2012, and among them 59.67% prevalence of head lice was observed. The height and weight for age was compared following 50th percentile or standard deviation score (SD?score) of WHO/ NCHS reference standard. In case of WAZ (weight for age using Z?score value) of boys, moderate malnutrition was found in 2, 3, and 5 years age group and mild malnutrition was found in 1, 4, 6 and 7 years age group. In case of WHZ (weight for height of boys), mild malnutrition was found in age group 2, 3 and 5 years. In better growth children, 56.67% were infested by head lice, 56% in medium growth children and the highest 65.46% among the children with mild growth. The intensity of infestation was mostly mild and moderate. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20091 Dhaka Univ. J. Biol. Sci. 23(2): 119-125, 2014